MENINGKATKAN INTERAKSI SOSIAL DAN MENGURANGI KETERGANTUNGAN GAWAI SELAMA LIBURAN SEKOLAH MELALUI PERMAINAN TRADISIONAL - Dennis Tambunan; Ary Mecky Prawira Ketaren; Edo Hamdani Oktavianus Sipayung; Tonazisoki Laia (Interaksi : Jurnal Pengabdian Kepada masyarakat, 2026)
Rapid technological advancements have shifted children's daily activities toward excessive use of digital devices, resulting in reduced social interaction. Traditional games play a significant role in fostering social skills and strengthening interpersonal interactions among children.This Community Service Program (PKM) aimed to enhance children's social interaction and reduce gadget addiction during the school holiday period. The program was designed to reintroduce children to traditional games, enabling them to recognize, understand, appreciate, preserve, and further develop their local cultural heritage while mitigating the negative effects of excessive gadget use. Traditional games were promoted as an alternative recreational activity during school holidays, allowing children to spend their leisure time in meaningful and socially engaging ways.The program was implemented in Dusun III Lubuk Jaya, Kwala Serapuh Village, involving 25 children as participants and university students as facilitators. It employed the Participatory Action Research (PAR) approach, which encourages the active involvement of all stakeholders throughout every stage of the program.The results demonstrated an improvement in children's social interaction and a reduction in gadget usage during the school holiday period. In addition, the program enhanced cooperation and communication among participants while playing traditional games. These findings indicate that traditional games are an effective strategy for reducing gadget addiction, rebuilding children's social interaction, and fostering values of cooperation and togetherness within the community.